Adsorption and desorption characteristics of chlorosulfuron in selected minerals and Pakistani soils - Khuram Shahzad Ahmad; Naghmana Rashid; Sundus Azhar (Eurasian Journal of Soil Science, 2016)
Sorption and desorption efficiency of Chlorosulfuron that is sulfonylurea herbicide was checked by selecting different minerals and two types of Pakistani soils that were different on spatial scale. In Pakistan, sulfonylurea herbicide is being used against wide varieties of broad leaf weeds and for some grasses as well. Results obtained after the experimental work showed that adsorption co-efficient isotherm for Chlorosulfuron in tested soils data well fitted the Freundlich equation. In all the cases, slope n<1 was resembling the C type curve and isotherm was nonlinear. Due to low adsorption, distribution co-efficient (Kd) parameters were also low. Results indicated that soil samples (silt loam) collected from northern hilly areas Ayubia, Khyber Pukhtunkhwa showed more adsorption for Chlorosulfuron herbicide i.e. 25.5% than the sandy soil of Multan Punjab. The major difference between the sorption capacities of both of the soil was due to the difference in soil organic matter and soil pH. Among both these factors, organic matter plays more significant role in sorption. Adsorption efficiency of synthesized compounds on different soil types of known composition can be predicted by the adsorption and desorption results of the present study.